Advances in Nano-Fertilizers and Nano-Pesticides in Agriculture: A Smart Delivery System for Crop Improvement - Jogaiah, Sudisha; Singh, Harikesh Bahadur; Fraceto, Leonardo Fernandes [UNESP]; de Lima, Renata (Elsevier, 2020)
Advances in Nano-fertilizers and Nano-pesticides in Agriculture: A Smart Delivery System for Crop Improvement explores the use of nanotechnology for the controlled delivery of pesticides, herbicides and fertilizers that improve the safety of products while also increasing the efficiency of food production and decreased environmental pollution. The development of nanodevices such as smart delivery systems to target specific sites, as well as nanocarriers for chemical controlled release are currently important aspects in novel agriculture and require a strong foundation of understanding, not only the technology, but also the resulting impacts.